Materials for Sustainability. - Salame, Chafic-Touma. (Zurich : Trans Tech Publications, Limited, 2022)
Special topic volume with invited peer-reviewed papers only.
Modeling and Validation of the Enthalpy-Temperature Curve for Phase Change Materials -- Chapter 6: Ecology Safety and Technologies of Environmental Engineering -- The Effect of Tidal Energies on the Materials Properties of the Soil at Southern Mesopotamia -- Spatial Analyzing of the Chemical Soil Properties for the Sanam Mountain- Al Zubair Region South of Basra Province and Diagnosis of its Effects on Soil Qualities Using Remote Sensing Technology and GIS -- Keyword Index -- Author Index
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Materials science -- Research; Materials -- Technological innovations; Science des matériaux -- Recherche; Matériaux -- Innovations; Materials science -- Research; Materials -- Technological innovations